ANALISIS PERBANKAN SYARIAH PENGARUH KUALITAS PELAYANAN MIKRO KREDIT SALES TERHADAP KEPUASAN KONSUMEN DAN DAMPAKNYA PADA MINAT PENGAMBILAN ULANG KREDIT DI BANK MANDIRI KANTOR CABANG PEMBANTU TAWES, JAKARTA - Munandar; Thantawi, Tubagus Rifqy; Mubarok, Mohamad Kharis (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
The purpose of this study was to determine the effect of Micro Credit Sales (MKS) Service Quality on Consumer Satisfaction and Its Impact on Interest in Credit Retrieval (Survey on Micro Credit Consumers at Bank Mandiri Tawes). The number of samples is 71 respondents. The results of this study state that: service quality has a positive effect on customer satisfaction which can be seen in the results of path analysis, the results of the equation model 1 are Y = 15.223 + 0.509 X + 0.630 Z and the equation model 2 is Z = 4.227 + 0.909 X , while the results of the t test in model 1 obtained the value of sig. 0.009 < 0.05 and t value 5.090 > 1.99495, it means that there is a significant influence between Service Quality on credit re-taking while for consumer satisfaction with credit re-taking is 0.000 < 0.05 and the t-value is 6.753 > 1.99495 which means there is an influence which is significant between consumer satisfaction with credit re-taking and in model 2 the results of the t test with a value of sig. 0.000 <0.05 and the t-count value is 11.916> 1.99495, it means that there is a significant influence between Service Quality on customer satisfaction. Furthermore, in the Sobel test, the z-value obtained is 4.567> 1.98 with a significance level of 5%, it proves that customer satisfaction significantly mediates the effect of service quality on credit withdrawal.